2008
DOI: 10.1093/imrn/rnn150
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Nevanlinna Theory and Ultradiscrete Equations

Abstract: A tropical version of Nevanlinna theory is described in which the role of meromorphic functions is played by continuous piecewise linear functions of a real variable whose one-sided derivatives are integers at every point. These functions are naturally defined on the max-plus (or tropical) semi-ring. Analogues of the Nevanlinna characteristic, proximity and counting functions are defined and versions of Nevanlinna's first main theorem, the lemma on the logarithmic derivative and Clunie's lemma are proved.As we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 26 publications
1
66
1
Order By: Relevance
“…Finally, we end this section with some remarks about a new suggested integrability detector. There have been some encouraging numerical results suggesting that Trpoical Nevanlinna theory might be used to comment on the integrability of ultra-discrete equations [40]. We end this note by giving some summarized remarks in section 5.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, we end this section with some remarks about a new suggested integrability detector. There have been some encouraging numerical results suggesting that Trpoical Nevanlinna theory might be used to comment on the integrability of ultra-discrete equations [40]. We end this note by giving some summarized remarks in section 5.…”
Section: Introductionmentioning
confidence: 94%
“…This term was first used by French mathematicians to honour their Brazilian colleague Imre Simon according to the authors of [41]. This semi-ring was first appeared in middle of the last century in Kleene's paper on nerve sets and automata according to [40]. Another semi-ring that is Idempotent and Tropical the min-plus semi-ring where…”
Section: The Max-plus Semi-fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical Nevanlinna theory may be understood as a cross-road between tropical mathematics and the classical Nevanlinna theory, see [17] for a general background of tropical mathematics and [8], [12] and [13] for the tropical setting of the Nevanlinna theory. Indeed, tropical Nevanlinna theory provides the flexibility of applying complex analysis methods to considering real functions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, tropical Nevanlinna theory provides the flexibility of applying complex analysis methods to considering real functions. Recall that Halburd and Southall [8] described continuous piecewise linear functions on R with one-side integer derivatives as tropical meromorphic functions, and established tropical versions of the first main theorem and the lemma on the logarithmic derivative. Laine and Tohge [13] then showed that tropical Nevanlinna theory also holds to piecewise linear functions with arbitrary real slopes, and obtained a tropical version of the second main theorem.…”
Section: Introductionmentioning
confidence: 99%